ENT 530 Case Study / Mohamad Alzafri Mohd Haniza ... [et al.] - Mohd Haniza, Mohamad Alzafri; Mohd Hamezan, Muhammad Amir Fahmi; Mohd Azhari, Muhammad Amir Syahmi; Murad, Muhammad Ammar Naim; Mohd Zahari, Muhammad Azri Syazwan (2019)
AR-RIQZ RESOURCES is a business of food sales and services, mainly operates in UiTM Puncak Alam. The business operates between 3.00p.m - 7.00 p.m, from Monday to Friday. Their main products are "nasi lemak" and "nasi ganja", which have received many good reactions and feed backs from regular customers residing in UiTM Puncak Alam. Besides running their main operation in Puncak Alam, the company also provides catering services for events such as wedding. The company has collaborated with JKM and Masjid Negeri for several times in the past few years, The business uses cash as their main medium of transaction. Customers can directly purchase their food at the operating location, or make earlier orders through Whatsapp. Despite having only three workers and four hours of operation a day, they are very efficient in preparing and servicing their customers. The company is 100% bumiputera. With their strong product "nasi lemak", and its famous and unique "sambal", the business currently has huge followings, with many customers describing the product as "uniquely different than others".